Caracterização petrográfica de corpos com mineralizações de ferro no Grupo Bom Jardim - Caçapava do Sul – RS – BR - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This paper will discuss the petrography of rocks with iron mineralization, inserted in the Bom Jardim Group (BJG) in Caçapava do Sul (RS-BR). The BJG is a volcanosedimentary unit, which occupies some 670 m thick in the western, Neoproterozoic Camaquã Subbasin of the São Gabriel Terrane (Dom Feliciano West Belt). The BJG is composed of sedimentary rocks and intermediate to basic igneous rocks with potassic alkaline affinity and pyroclastics. This group is subdivided into three formations from the base, Cerro da Angelica Formation, Hilário Formation, and Picada das Graças Formation. The objective of this study is to petrographically characterize the rocks with iron mineralization from the study in the Bom Jardim Group. In order to reach the objective proposed in this study, there was a pre-field stage, where the bibliographical review was carried out, a field stage, where three field days were held, two for sample collection for the making of petrographic thin section and one for the identification of the surrounding rocks, and a post-field stage, where the macro and microscopic descriptions were made. The results of the identification of the surrounding rocks generated a point and lithological map where it is possible to observe that the rocks of the study outcrop in the drainage and the surrounding rocks of the Hilário Formation and Picada das Graças Formation surround them. The results of the petrography, show that the rocks of the study present a mineralogy composed mainly of quartz and hematite/magnetite intercalated between micro to mesobands. Two facies were identified, the oxide facies with predominance of hematite/magnetite over quartz, which preserved the primary banding of the rock and the silicate facies, which predominates quartz over hematite/magnetite and presents a secondary banding generated by metastomatism and tectonic. The results obtained through petrography in the study, suggest that the study rocks can be characterized as BIF’s or as iron mineralization in the sandstones of the Picada das Graças Formation. However major and minor element geochemical studies, detailed mineral chemistry (mev, microprobe), isotopy of unstables and dating would be needed to really prove if these rocks are BIF’s as well as the type of BIF’s. Thus the hypothesis of being iron mineralization in the form of hematite/magnetite veins, intercalated between the quartz bands would be the most accepted in this study.
Keywords: Formação Ferrífera Bandada; Petrografia; Banded Iron Formation; Petrography; CNPQ::CIENCIAS EXATAS E DA TERRA